Optimal patient selection for simultaneous heart‐kidney transplant: A modified cost‐effectiveness analysis. Issue 4 (30th November 2021) - Wayda, Brian; Cheng, Xingxing S.; Goldhaber‐Fiebert, Jeremy D.; Khush, Kiran K.
Abstract : Increasing rates of simultaneous heart‐kidney (SHK) transplant in the United States exacerbate the overall shortage of deceased donor kidneys (DDK). Current allocation policy does not impose constraints on SHK eligibility, and how best to do so remains unknown. We apply a decision‐analytic model to evaluate options for heart transplant (HT) candidates with comorbid kidney dysfunction. We compare SHK with a "Safety Net" strategy, in which DDK transplant is performed 6 months after HT, only if native kidneys do not recover. We identify patient subsets for whom SHK using a DDK is efficient, considering the quality‐adjusted life year (QALY) gains from DDKs instead allocated for kidney transplant‐only. For an average‐aged candidate with a 50% probability of kidney recovery after HT‐only, SHK produces 0.64 more QALYs than Safety Net at a cost of 0.58 more kidneys used. SHK is inefficient in this scenario, producing fewer QALYs per DDK used (1.1) than a DDK allocated for KT‐only (2.2). SHK is preferred to Safety Net only for candidates with a lower probability of native kidney recovery (24%–38%, varying by recipient age). This finding favors the implementation of a Safety Net provision and should inform the establishment of objective criteria for SHK transplant eligibility. Abstract : A decision‐analytic model shows that, for most candidates, simultaneous heart‐kidney transplant is inefficient from a societal standpoint compared to heart‐alone transplant with an accompanying Safety Net provision.